2007
DOI: 10.1109/twc.2007.060339
|View full text |Cite
|
Sign up to set email alerts
|

Recovering Multiplexing Loss through Successive Relaying Using Repetition Coding

Abstract: In this paper, a transmission protocol is studied for a two relay wireless network in which simple repetition coding is applied at the relays. Information-theoretic achievable rates for this transmission scheme are given, and a space-time V-BLAST signalling and detection method that can approach them is developed. It is shown through the diversity multiplexing tradeoff analysis that this transmission scheme can recover the multiplexing loss of the half-duplex relay network, while retaining some diversity gain.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
277
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(279 citation statements)
references
References 35 publications
2
277
0
Order By: Relevance
“…Based on the analysis provided above, it is concluded that both inequalities (35) and (38) must be satisfied to allow the 'actively cooperative scheme' achieve a higher capacity with less transmit power, compared to the 'passively cooperative scheme', if the three stations collaborate. The channel capacity of the passively and actively cooperative schemes is shown in Fig.…”
Section: Transmit Powermentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the analysis provided above, it is concluded that both inequalities (35) and (38) must be satisfied to allow the 'actively cooperative scheme' achieve a higher capacity with less transmit power, compared to the 'passively cooperative scheme', if the three stations collaborate. The channel capacity of the passively and actively cooperative schemes is shown in Fig.…”
Section: Transmit Powermentioning
confidence: 99%
“…Both these schemes impose, however, a factor two multiplexing loss because of splitting a time slot into two phases: broadcasting and relaying, as described in Section 4. To recover the multiplexing loss, successive relaying was employed in [35,36], which may also be applied to our scheme.…”
Section: Transmit Powermentioning
confidence: 99%
“…To mitigate this time loss, a successive relaying protocol was proposed in [7]. Kong et al [12] employed a successive relaying technique, which was capable of approaching the relay-aided link's capacity.…”
Section: A Successive Relaying Aided Coopmacmentioning
confidence: 99%
“…However, in most three-terminal cooperative scenarios, a significant multiplexing loss will be incurred compared to direct transmissions due to the half-duplex constraint of practical transceivers. For the sake of recovering the multiplexing loss, a successive relaying protocol was proposed in [5] by incorporating an additional relay in the network and arranging for the two relays to transmit in turn. However, a sophisticated channel code was required for achieving near-error-free detection at the relay nodes and hence to prevent errorpropagation, which was not considered in [5].…”
Section: A Backgroundmentioning
confidence: 99%